Induction of IL-12 Production in Human Peripheral Monocytes by Trypanosoma cruzi Is Mediated by Glycosylphosphatidylinositol-Anchored Mucin-Like Glycoproteins and Potentiated by IFN-γ and CD40-CD40L Interactions. (9th July 2014) - Abel, Lúcia Cristina Jamli; Ferreira, Ludmila Rodrigues Pinto; Cunha Navarro, Isabela; Baron, Monique Andrade; Kalil, Jorge; Gazzinelli, Ricardo Tostes; Rizzo, Luiz Vicente; Cunha-Neto, Edecio
Abstract : Chagas disease, caused by the protozoan parasite Trypanosoma cruzi ( T. cruzi ), is characterized by immunopathology driven by IFN- γ secreting Th1-like T cells. T. cruzi has a thick coat of mucin-like glycoproteins covering its surface, which plays an important role in parasite invasion and host immunomodulation. It has been extensively described that T. cruzi or its products—like GPI anchors isolated from GPI-anchored mucins from the trypomastigote life cycle stage (tGPI-mucins)—are potent inducers of proinflammatory responses (i.e., cytokines and NO production) by IFN- γ primed murine macrophages. However, little is known about whether T. cruzi or GPI-mucins exert a similar action in human cells. We therefore decided to further investigate the in vitro cytokine production profile from human mononuclear cells from uninfected donors exposed to T. cruzi as well as tGPI-mucins. We observed that both living T. cruzi trypomastigotes and tGPI-mucins are potent inducers of IL-12 by human peripheral blood monocytes and this effect depends on CD40-CD40L interaction and IFN- γ . Our findings suggest that the polarized T1-type cytokine profile seen in T. cruzi infected patients might be a long-term effect of IL-12 production induced by lifelong exposure to T. cruzi tGPI-mucins.